COAL MINING INVESTMENT OPPORTUNITIES IN INDONESIA ON GOVERENMENT REGULATION NUMBER 3 OF THE YEAR 2020 CONCERNING MINERAL AND COAL MINING - Andi Batubara; Amiludin Amiludin; muhammad Asmawi (Indonesian Journal of Law and Policy Studies, 2021)
The coal mining industry has part of the important economic role to support National Budgeting government, therefor need to support haven’t overlapped by the regulation, to support easy in permitted so it will able to feel more the value-added for government, nation, and society